Эстетическое преобразование среды как педагогический инструмент воспитания учащихся (опыт реализации практико-ориентированной теории) - Боровская, Е.В. (My University, 2013)
Our understanding of upbringing role of the environment is based on the methodological principles of the theory of environmental approach (Y.S. Manuylov). From these positions we come to the consideration of aesthetic changes taking place in secondary school №1 g. Semenov, Nizhny Novgorod region. For us it is important that the environment of the educational institution became the means of updating of the students. Environment appears pedagogical means, if its influence provides necessary to achieve the pedagogical result of the lifestyle of the students. Accordingly, the lifestyle helps to find the value of the environment.